Feasibility of Revising the Quality Standard for Δ9-Tetrahydrocannabinol Content in Cannabis Inflorescence within Thai Herbal Pharmacopoeia - Charoonratana, Tossaton; Thongmuenwaiyathorn, Ratsarin; Achsorn, Chayanee; Weachasdorn, Thongnoppakhun; Songsak, Thanapat (Interprofessional Journal of Health Sciences, 2025)
Cannabis (Cannabis sativa L.) is a plant that is widely cultivated in Thailand. It has been used for both traditional and contemporary medical conditions. Referencing the THP 2021, the standard for cannabis inflorescence in Thailand requires a minimum 1% w/w THC content. The lack of an upper THC limit risks high-potency cannabis inflorescence entering the supply chain. Compounding requires dose adjustment, but allowing high-THC batches, which are often unnecessary, exacerbates prescriber workload and amplifies the consequences of any dosing mistake. Establishing an upper THC limit for cannabis inflorescence is therefore crucial. Thus, the authors conducted an integrated review with policy recommendation to support this concept. The review utilized data sourced from Google Scholar and reliable information obtained from governmental agencies. Based on this study, both safety and efficacy data indicate that cannabis inflorescence as a raw material with low THC content is sufficient for treating patients with Thai landraces providing sufficient potency. This contrasts with most hybrid strains, which contain THC levels deemed excessive. Therefore, the authors propose that appropriate use of cannabis inflorescence can be achieved by setting THC criteria to reflect the range found in Thai cannabis strains (e.g., 1-12% w/w) exclusively for the production of Thai Traditional Drugs originating from ancient medical texts, thus aligning with Thai Traditional Medicine wisdom. Conversely, the original criteria should apply to inflorescence used in the manufacture of other products. These preventive measures constitute a patient right and align with the legal status of cannabis inflorescence as a controlled herb in Thailand.